2018
DOI: 10.1016/j.neuroimage.2017.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating g-ratio weighted changes in the corpus callosum as a function of age and sex

Abstract: Recent years have seen a growing interest in relating MRI measurements to the structural-biophysical properties of white matter fibers. The fiber g-ratio, defined as the ratio between the inner and outer radii of the axon myelin sheath, is an important structural property of white matter, affecting signal conduction. Recently proposed modeling methods that use a combination of quantitative-MRI signals, enable a measurement of the fiber g-ratio in vivo. Here we use an MRI-based g-ratio estimation to observe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 82 publications
13
89
1
Order By: Relevance
“…levels have tract specific values in the range 0.67-0.76, consistent with previous findings in younger adults(20-40 years;Cercignani et al, 2016). PD-based estimates of the g-ratio do not require calibration(Berman et al, 2017;Duval et al, 2017) and differences arising from such a comparison might highlight changes in macromolecular content with age.Our findings suggest that the largest investments in myelination for a given axonal caliber occur in the anterior callosal fibers (forceps minor) while conversely the lowest myelination investments occur in Projection and callosal fiber trajectories for FA, MD, ICVF, and ODI. A comparison between the g-ratio aging trajectories shown here and those calculated from myelin volume fraction obtained from PD estimates would be of high interest.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…levels have tract specific values in the range 0.67-0.76, consistent with previous findings in younger adults(20-40 years;Cercignani et al, 2016). PD-based estimates of the g-ratio do not require calibration(Berman et al, 2017;Duval et al, 2017) and differences arising from such a comparison might highlight changes in macromolecular content with age.Our findings suggest that the largest investments in myelination for a given axonal caliber occur in the anterior callosal fibers (forceps minor) while conversely the lowest myelination investments occur in Projection and callosal fiber trajectories for FA, MD, ICVF, and ODI. A comparison between the g-ratio aging trajectories shown here and those calculated from myelin volume fraction obtained from PD estimates would be of high interest.…”
supporting
confidence: 88%
“…One such quantitative magnetic resonance imaging (qMRI) methodology-multiparameter mapping (MPM; Weiskopf et al, 2013), provides estimates for the magnetization transfer (MT) and relaxation rates R1 and R2*, each providing a level of sensitivity to local myelination and/or iron deposi- Draganski et al, 2011), particularly in later life after myelination has matured to a peak density before reversing in trend and declining with age (Li et al, 2014;Yeatman et al, 2014). Preliminary investigations of g-ratio change across the life span in small imaging cohorts (n = 38-92) have reported linear increases with age in the deep WM (Cercignani et al, 2016), with little age-related change observed across the mid-sagittal portion of the corpus callosum (Berman, West, Does, Yeatman, & Mezer, 2017). Preliminary investigations of g-ratio change across the life span in small imaging cohorts (n = 38-92) have reported linear increases with age in the deep WM (Cercignani et al, 2016), with little age-related change observed across the mid-sagittal portion of the corpus callosum (Berman, West, Does, Yeatman, & Mezer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The difference between MVF imaging markers was particularly strong in the corticospinal tract. While both imaging markers have been previously used as proxy for myelin density (MT [Mohammadi et al, ], MTV [Duval et al, ]), there is only direct comparison with ex vivo histology gold standard for MTV [Berman et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…We also used mrQ to calculate two additional quantitative brain maps: the lipid and macromolecular tissue volume (MTV) map (Mezer et al, , ), which uses the proton density signal to determine the amount of nonwater per voxel; and the water‐surface interaction rate (SIR) map, which estimates the spin‐lattice relaxation rate normalized by nonwater tissue volume and reflects differences in tissue composition (Mezer et al, ). Finally, we used mrQ to synthesize a bias‐free T1‐weighted image from the qMRI data (Berman, West, Does, Yeatman, & Mezer, ; Gomez et al, ; Yeatman, Wandell, & Mezer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Since different readout schemes produce different geometrical artifacts, we used ANTs to warp the nondiffusion quantitative maps into the diffusion space. (For further discussion and examples, see Berman et al, ; Yeatman, Wandell, & Mezer, ). Finally, the tract profile for each metric was calculated by performing a weighted averaging of the corresponding points, such that points closer to the core count more than points farther away.…”
Section: Methodsmentioning
confidence: 99%